The shadow economy factors and causes analysis by expert evaluation method: case of Lithuania - Krumplytė, Jolita (Business, Management and Economics Engineering, 2010)
In the scientific literature the shadow economy is defined as a complex multifaceted set of phenomena, whose existence is determined by various factors and causes. The article examines the shadow economy through tax administration perspective. The author’s chosen object of the research encompasses economic activities, results of which such as tax evasion or concealment are not included in the official records. The shadow economy factors and reasons are economic, legal-administrative and social- psychological. Most of the time scientific research analyses the following shadow economy factors and causes: ▪ burden and rise of direct and indirect taxes and compulsory social insurance contribution; ▪ too stringent (or insufficient) legal and administrative regulation; ▪ weak government and a high level of corruption in the governmental sector; ▪ the income inequality (a high poverty level); ▪ the legislative gaps; ▪ the tax administration system deficiencies; ▪ irrational country’s economic policy; ▪ tax morale; ▪ insufficient government attention to social policy or irrational its development. The article presents the empirical study results about Lithuanian shadow economy factors and causes. The survey was carried out by experts – Lithuanian State Tax Inspection staff which has experience in inspecting taxpayers and conducting tax investigations. 702 experts took part in the research. According to experts’ estimations, companies and individuals enter into shadow economic activity mainly because they do not have any other way out (otherwise they won’t be able to stand up to competition, individuals won’t be able to make a living, etc.) as well as because other economy players pull them in. Experts also estimate that the most important Lithuanian shadow economy causes are the following: too big tax burden (in the case of illegal work – significant gross and net wage gap), gaps in legislation, frequent law changes, distrust of country’s government, dissatisfaction with the quality of work of governmental institutions. The main causes of the sprawl of the shadow economy – the inability to compete without being involved in the shadow economy, the lack of unified declaration of income and insufficient control of state institutions.Article in Lithuanian.Šešėlinės ekonomikos veiksnių ir priežasčių tyrimas ekspertinio vertinimo metodu: Lietuvos atvejis